2002
DOI: 10.1097/00007890-200209270-00014
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus seromismatching increases the risk of acute renal allograft rejection.

Abstract: Patients who are CMV seromismatched are at higher risk of acute renal allograft rejection. This finding suggests that CMV infection or disease is a risk factor for acute rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 18 publications
2
25
1
1
Order By: Relevance
“…and acute rejection of established allografts (1)(2)(3)(4). Experimental animal models have revealed that the exposure of hosts to viral or parasitic agents prior to transplantation can result in the development of memory T cells (5)(6)(7) that are resistant to the effects of anti-CD154 therapy (8,9).…”
Section: Linical Data Support a Correlation Between Viral Infectionsmentioning
confidence: 99%
“…and acute rejection of established allografts (1)(2)(3)(4). Experimental animal models have revealed that the exposure of hosts to viral or parasitic agents prior to transplantation can result in the development of memory T cells (5)(6)(7) that are resistant to the effects of anti-CD154 therapy (8,9).…”
Section: Linical Data Support a Correlation Between Viral Infectionsmentioning
confidence: 99%
“…Furthermore, most studies have indicated that successful antiviral prophylaxis has a beneficial effect on long-term graft function (8). This suggests that viral replication is a component of risk, but the precise mechanisms underlying this effect are debated (9,11,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Although CMV prophylaxis can reduce the risk of CMV disease and associated mortality, its effects on allograft loss and acute transplant rejection have not been clearly established [12]. Many reports have demonstrated that CMV serostatus-that is, "seropositive or seronegative," as defined by conventional classifications-influences clinical outcome in renal transplantation [7,8]. For example, the combination of CMV-seronegative transplant recipients (RĎŞ) with CMVseropositive transplant donors (D+) led to the highest risk of CMV disease.…”
mentioning
confidence: 99%